Bird report, January 2 to May 23, 1978 - Brewer, Marion M.et al (1978)
Field report titled "Bird report, January 2 to May 23, 1978," submitted by Marion M. Brewer, May 23, 1978. Notes underlined mention the sightings of 56 Eared Grebes at Storm Lake and an large number of Black Terns. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of spring, 1978. Epson - sheet feed/flatbed